Insertion Sequence IS26 Reorganizes Plasmids in Clinically Isolated Multidrug-Resistant Bacteria by Replicative Transposition - He, Susu; Hickman, Alison Burgess; Varani, Alessandro M. [UNESP]; Siguier, Patricia; Chandler, Michael; Dekker, John P.; Dyda, Fred (Amer Soc Microbiology, 2015)
Carbapenemase-producing Enterobacteriaceae (CPE), which are resistant to most or all known antibiotics, constitute a global threat to public health. Transposable elements are often associated with antibiotic resistance determinants, suggesting a role in the emergence of resistance. One insertion sequence, IS26, is frequently associated with resistance determinants, but its role remains unclear. We have analyzed the genomic contexts of 70 IS26 copies in several clinical and surveillance CPE isolates from the National Institutes of Health Clinical Center. We used target site duplications and their patterns as guides and found that a large fraction of plasmid reorganizations result from IS26 replicative transpositions, including replicon fusions, DNA inversions, and deletions. Replicative transposition could also be inferred for transposon Tn4401, which harbors the carbapenemase bla(KPC) gene. Thus, replicative transposition is important in the ongoing reorganization of plasmids carrying multidrug-resistant determinants, an observation that carries substantial clinical and epidemiological implications for understanding how such extreme drug resistance phenotypes evolve. IMPORTANCE Although IS26 is frequently reported to reside in resistance plasmids of clinical isolates, the characteristic hallmark of transposition, target site duplication (TSD), is generally not observed, raising questions about the mode of transposition for IS26. The previous observation of cointegrate formation during transposition implies that IS26 transposes via a replicative mechanism. The other possible outcome of replicative transposition is DNA inversion or deletion, when transposition occurs intramolecularly, and this would also generate a specific TSD pattern that might also serve as supporting evidence for the transposition mechanism. The numerous examples we present here demonstrate that replicative transposition, used by many mobile elements (including IS26 and Tn4401), is prevalent in the plasmids of clinical isolates and results in significant plasmid reorganization. This study also provides a method to trace the evolution of resistance plasmids based on TSD patterns.